Reconceptualizing Communication for Moral Education in Islam through Dialogic Engagement - Mayasari, Eka (Feedback International Journal of Communication, 2025)
Moral education in Islam emphasizes the development of akhlaq (Islamic character), yet pedagogical strategies to internalize these values often rely on monologic instruction. This study explores dialogic engagement as a transformative communication model for Islamic moral education. Using a qualitative library research method, this study analyzed classical Islamic texts, contemporary moral education theories, and recent empirical studies on communication and character development. Content and thematic analysis were applied to synthesize key concepts and pedagogical practices. Findings indicate that dialogic communication through reflective dialogue, interactive Q&A, and value clarification facilitates the internalization of moral values by enhancing critical thinking, empathy, and ethical awareness. When supported by inclusive learning environments and integrated with narrative and demonstrative strategies, dialogic engagement promotes holistic moral development. The study positions dialogic engagement as both a prophetic tradition and a contemporary pedagogical need. It concludes that dialogic methods enable value co-construction between educators and learners. However, empirical research is needed to test its practical application across diverse Islamic educational settings.